Testing the three- and four-factor models of the Korean version PCL-R as predictors of two antisocial outcomes – recidivism and risk. Issue 5 (28th May 2017) - Sohn, Ji Seun; Lyons, Phillip; Menard, Scott; Lee, Soo Jung
ABSTRACT: Psychopathy has consistently been associated with antisocial outcomes. The three- and four-factor models have been best fitted to data relating to Korean serious offenders ( N = 451), offering construct validity of the Korean Psychopathy Checklist-Revised (PCL-R). However, no study has yet tested the predictive power of the Korean PCL-R to explain two different types of antisocial outcomes: (1) risk of inmates measured by correctional officers during incarceration and (2) recidivism after release. By exploring these two forms of antisociality, here we sought to establish the predictive and construct validities of the Korean version of PCL-R. We found that the deviant lifestyle (Factor 3) performed best for predicting both antisocial forms (risk and recidivism) and that the deficits in interpersonal (Factor 1) and affective (Factor 2) abilities also uniquely predicted one subtype of risk, which suggests the three-factor model is better than the four-factor model in predictions. These findings will be useful for criminal justice experts and practitioners in Korea.